(untitled) (International Journal of Innovative Technologies in Economy, 2019)
The article studies the financial market in the context of the modern approach to the development of the secondary market in Uzbekistan. The author explores the main problems in the development of the secondary market, and also offers a new practical approach to the development of methods to eliminate existing problems. The achieved scientific results allow us to formulate conceptual approaches to the study of the financial market as an object of state regulation.